PENGARUH JUMLAH PENDUDUK, PERTUMBUHAN EKONOMI, DAN UPAH MINIMUM PROVINSI (UMP) TERHADAP TINGKAT PENGANGGURAN DI PULAU SUMATERA - Berliana Putri Meilani Nasution; Syaparuddin; Jaya Kusuma Edy (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to analyze the trends and the simultaneous and partial influence of Population, Economic Growth, and the Provincial Minimum Wage (UMP) on the Unemployment Rate across Sumatera Island for the period 2006 to 2024. A quantitative approach was employed using panel data analysis (combining time series and cross-section data) covering 10 provinces in Sumatera Island. Secondary data was sourced from the official publications of the Central Statistics Agency (BPS). Based on the Chow and Hausman test results, the Fixed Effect Model (FEM) was selected as the appropriate estimation model. The F-test results indicate that Population, Economic Growth, and UMP simultaneously have a significant influence on the Unemployment Rate in Sumatera Island. The t-test (partial) revealed the following findings: (1) Population was found to have a negative and significant effect on the Unemployment Rate, suggesting that population growth alleviates pressure on the labor market. (2) Economic Growth had a negative and significant effect on the Unemployment Rate, supporting the theory that increased production absorbs more labor. (3) Provincial Minimum Wage (UMP) was also found to have a negative and significant effect on the Unemployment Rate. This contradicts classical theory but is explained by the push for higher labor participation and increased regional purchasing power.